Leaching of Organic Carbon in Micro Catchment Oil Palm Plantation Area PT Perkebunan Nusantara VI Jambi: Pencucian Karbon Organik pada Mikro DAS Lahan Perkebunan Kelapa Sawit PT Perkebunan Nusantara VI Jambi - Septiawan, Ginanjar Ika; Wahjunie, Eni Dwi; Murtilaksono, Kukuh; Sulaeman, Yiyi (Jurnal Ilmu Tanah dan Lingkungan, 2020)
Land use change can affect the ecosystem and regional hydrology. It increase the erosion and surface runoff of the land, especially the land that is not in line with the principles of soil and water conservation. The high rainfall affects the leaching process of carbon and nutrients from agricultural land to the river body. The leaching process of organic carbon and nutrients in the river need to be researched. It predicts the concentration of organic carbon and nutrients in the river, and it can be the indicator in monitoring of the land degradation. This research applied field experiment which used survey method with explorative descriptive for purposive sampling. This study showed that the location of leaching the most organic carbon formed DOC, nitrate, Al3+, and Mn2+ is point C. The rainfall has less significant effect in increasing stream discharge (r = 0.58). Stream discharge and dissolved ion concentration in the outlet (DOC, NO3-, PO43-, Fe2+, and Al3+) has no positive correlation. DOC concentration in the river has positive correlation with Fe2+ (0.94) and Al3+ (0.96). The multi stepwise regression model produces DOC = 2.48 + 0.90 Al3+ + 3.17 Fe2+ with the quite high value of R2 Adj. (0.94). It showed that DOC has affected Al3+ and Fe2+  by 94%.